Pandu Roga w.s.r. to Iron Deficiency Anaemia-A Conceptual Study. - Patidar, Deepika; Joshi, Ram Kishor; Sahu, Ajay Kumar; Panwar, Santosh; Babulal (International Research Journal of Ayurveda & Yoga, 2023)
In this disease there is predominance of paleness all over the body. Due to its similarity, it can be co-related with modern disease anaemia. In Ayurveda, Pandu Roga is a pallor on the skin produced by a quantitative and qualitative Rakta dhatu deficit manifested as a lack of haemoglobin and/or red blood cells. Rasavaha and Raktavahasrotas are the most important in the pathophysiology of Pandu Roga. The changing lifestyle of humans via Ahara and Vihar has a significant impact in the emergence of many ailments. Pandu Roga is one among them as well. Ama is formed as a result of our poor food choices and lifestyle, which then leads to Agnimandya and, finally, Amayukta Ahararasa. Rasa Dhatu Utpatti is hampered, and Pandu Roga manifests. Aggravated Pitta is responsible for the creation of Posaka (nutrient component) from the Rasadhatu, which causes Rakta depletion. Inadequate dietary intake, quick development, low birth weight, and gastrointestinal losses caused by increased cow’s milk consumption are the most prevalent causes of iron insufficiency in children. According to WHO, anaemia affects one-quarter of the world’s population and is most prevalent in pre-school-aged children and women. In children, anaemia varies from 45 to 65%. Pallor, weariness, lack of appetite, palpitations, irritability, weakness, dyspnoea, brittle nails, pica, headache are all clinical manifestations of the condition. According to Ayurveda, the main goal of therapy is to rectify and balance Agni, which allows metabolism to be controlled.